An investigation into conditions that enable or constrain sustainable paper usage at Rhodes University - Mfenyana, Nondumiso Gloria (Rhodes University, Faculty of Commerce, Rhodes Business School, 2013)
The interest in this study was initiated by the rapid global transition of paper usage to digital systems in teaching and learning at tertiary institutions, particularly those that are signatories to the Talloires Declaration, which include Rhodes University (RU). It was discovered that there are two earlier studies (Leslie et al. 2009; Amutenya et al. 2009) that investigated and proposed recommendations towards sustainable paper usage at Rhodes University (RU). This study then investigated the response of RU to the proposed recommendations of the above mentioned studies and evaluated the conditions that promote and constrain sustainable paper usage in teaching and learning, and the attitudes of users thereof.
Keywords: Colleges and Universities -- Environmental aspects -- South Africa Paper; Waste paper -- Recycling